Why It’s Important to Advance STEAM in Mathematics Classroom (PRISMA, Prosiding Seminar Nasional Matematika, 2021)
This article explains about how is the positive impact in advancing STEAM Education in mathematics classrooms. The discussion starts with the fact that STEM education has received much attention to achieve the competencies needed in the 21st century in the last decades. However, STEM education, which tends to override arts education, encourages reforms in this approach. Seeing the importance of art education as a basis for developing creativity and character in society gives a chance for STEAM education and integration of STEM education with art education, which is believed to impact students' learning achievement and engagement positively. As one of the integration components in STEAM, mathematics will get a positive impact too. Mostly by looking at the fact that the students' ability in mathematics competence is still low refers to the result of the national exam, AKSI, PISA, and TIMSS. Some of the main reasons why it's important to advance STEAM education in mathematics classroom include honing high order analytical thinking skills (HOATS), honing students' C2PC abilities, and enhancing students' engagement in the mathematics classroom.